Parents and children about sexual education - Costin, Alina (Technium Social Sciences Journal, 2021)
As Jankovic, Malatestinic and Striehl, (2013) point out, sexuality is a key dimension of youth development, with important implications for mental and physical health. Parents are a relevant source of information about sexuality, they have the ability to shape their children's values and behaviour about this dimension of their wealth, and they are also responsible for transmitting this information in the most accurate and positive format possible (Fitzharris & Werner-Wilson, 2004; Ashcraft, Murray, 2017;). In Romanian society, the parents of today's teenagers were educated in the socialist era, in fact, the context in which they lived did not encourage free discussions on sexual issues neither with their parents, nor in school. Sex education was limited to abstinence, the subject being taboo in Romanian families (Mocanu, 2018). Starting from these realities, we conducted a research on assessing the perception of the parent-child couple on the subject of sex education. 82 families of high school teenagers were surveyed about their perceptions of adolescent sex education, its benefits and its role in preventing dropout. The results indicate that adolescents give more realistic meanings to the meaning of sex education than their parents. There is a higher score of parents who appreciate that sex education has no benefits for children, on the contrary. The paper makes suggestions on the need to implement intervention programs that involve parents in a series of strategies that complement discussions about sex, and develop a support system (Miller, 1998, Izugbara, 2008; Ballard, & Gross, 2009).